Injuries among professional ballet dancers in Finland: a prospective cohort study over five ballet seasons (FinBallet Study) - Pasanen, K.; Alanko, L.; Osmala, J.; Kenny, S. J.; Vasankari, T.; Aaltonen, S. (The Physician and Sportsmedicine, 2025)
Objective The aim of this prospective cohort study was to examine the incidence and characteristics of injuries in professional ballet dancers across multiple seasons.